البيداغوجية النقدية (الاتجاه الجديد في تعليم اللغة العربية لغير الناطقين بها) - Muhammad Muchlish Huda (Abjadia, 2018)
تهدف هذه المقالة الى أن تقوم بمناقشة حيويّة في مجال البيداغوجية النقدية كإحدى المقاربات فيما بعد الحداثة في التعليم اللغة. فتحاول هذه المقاربة الى أن تقوم بالإرتباط المتين بين السياق الدراسي والسياق الإجتماعي لتشدّد تمكين المتعلمين على التفكير والتصرّف بشكل حاسم بهدف تحويل ظروفهم الحياتية والشعبية. فتعتمد هذه النظرية بمباديئ رئيسية من فرانكفورط الأكاديمي كالمصادر الأولوية الا وهي نظرية نقد الإجتماعية والنظم السياسي والمجتمعة المغرضة لأنها نتيجة من حركة الإجتماعية الحارة في فرانكفورط “Frankfurt” الألماني سنة 1923. تتعلق هذه النظرية بمصطلح جدلية البيداغوجية “Dialogic Pedagogy” أشاره Paulo Freire  في مؤلفاته أو باللغة العربية أن في التعليم يلزم على الجدلية, فليس هناك الحوار بلا جدلية وليس هناك التعليم الصالح بلا الحوار. فظهور نظرية البيداغوجية النقدية في أمريكا من خلال فكرة غيروق في مجال التربية والبيداغوجية. لتحقيق هذا الهدف فيقوم الباحث على منهج البحث المكتبي حيث يقارن فيه كتب ومقالات علمية فيما تتعلق بهذه القضية. دلّت نتيجة هذه المقالة على أهمية تطبيق هذه المقاربة في تعليم اللغة لغير الناطقين بها وخصوصا في تعليم اللغة العربية لتزويد المتعلمين للحصول على وعي صالح وعناية جدّيّة في تنمية التساؤلات المتعلّمين وتحدى على المعتقدات والتطبيقات المهيمنة من خلال تعليم اللغة العربية. This paper aim to present the discursive dynamics of critical pedagogy theory as one of the post-modernism approaches in language learning. The critical pedagogy approach seeks to focus on the interrelationships that occur between the educational and social context with the aim of optimizing students' critical thinking reasoning as an agent of change. Critical pedagogy theory is based on the basic principles of the Frankfurt Academy as the primary source, especially the teachings on the theory of social criticism from the social movements in Germany 1923. This theory has a connection with the concept of "dialogic pedagogy" by Paulo Freire. Critical pedagogy emphasis on the process of dialogue in learning, including learning Arabic. Without dialogue and critical and discursive reasoning processes, the learning process becomes unhealthy. The critical pedagogies in America is often associated with Henry Giroux. This study uses a qualitative research method with a library approach. The research step is to collect information and research discourses relating to the theory of critical pedagogy. The results there is importance to use critical pedagogy in learning Arabic language to sharpen critical reasoning learners so that Arabic learners are not easily infiltrated with ideological orthodoxy and orthopraxies contained in learning material.